2022
DOI: 10.1039/d2sc04223a
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironment engineering of supported metal nanoparticles for chemoselective hydrogenation

Abstract: Selective hydrogenation with supported metal catalysts widely used in the production of fine chemicals and pharmaceuticals often faces a trade-off between activity and selectivity, mainly due to the inability to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 135 publications
1
6
0
Order By: Relevance
“…As disclosed, metal@zeolite can adjust the catalytic selectivity by strengthening the adsorption energy of target reactants while weakening the interaction of intermediates and products. 16,17 For example, the synthesized SOD zeoliteencapsulated Pd nanoclusters showed an ethylene selectivity of more than 94.5% in catalytic hydrogenation of acetylene via hydrogen spillover, and as reported by authors, compared to a bare Pd surface which possesses strong interaction energy with ethylene leading to low selectivity, easy desorption of ethylene from the SOD zeolite surface played a key role in promoting such high selectivity. 16 T h i s c o n t e n t i s In addition to selectivity, in the process of zeolitic hydrogen spillover, the adsorption capacity of the substrate on the surface of zeolite also has a significant effect on the catalytic activity.…”
Section: Introductionsupporting
confidence: 56%
“…As disclosed, metal@zeolite can adjust the catalytic selectivity by strengthening the adsorption energy of target reactants while weakening the interaction of intermediates and products. 16,17 For example, the synthesized SOD zeoliteencapsulated Pd nanoclusters showed an ethylene selectivity of more than 94.5% in catalytic hydrogenation of acetylene via hydrogen spillover, and as reported by authors, compared to a bare Pd surface which possesses strong interaction energy with ethylene leading to low selectivity, easy desorption of ethylene from the SOD zeolite surface played a key role in promoting such high selectivity. 16 T h i s c o n t e n t i s In addition to selectivity, in the process of zeolitic hydrogen spillover, the adsorption capacity of the substrate on the surface of zeolite also has a significant effect on the catalytic activity.…”
Section: Introductionsupporting
confidence: 56%
“…In addition, the properties of the surrounding microenvironment might affect the photocatalytic performance of the as‐prepared CMP photocatalysts. [ 34 ] Herein, we have designed and synthesized four kinds of novel donor‐acceptor CMPs from PCZN‐2 to PCZN‐5 through nickel(0)‐catalyzed Yamamoto cross‐coupling using 3,6‐dibromo‐9‐(4‐bromophenyl)carbazole (CZ) as electron donor and 5,5'‐dibromo‐2,2'‐bipyridine (DBPy) as electron acceptor. As a comparison, PCZN‐1 and PCZN‐6 were obtained by Yamamoto homocoupling reaction of CZ and DBPy, respectively.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…It has been reported that microenvironment regulation would significantly affect the chemoselective hydrogenation performance. 52 Next, the research progress will be introduced from the following four aspects: active components, supports, specially structured catalysts and promoters.…”
Section: Emerging Thermal Catalysts For Eg Synthesismentioning
confidence: 99%